PENERAPAN BIMBINGAN KELOMPOK SECARA DARING MELALUI TEKNIK SELF MANAGEMENT UNTUK PROKRASTINASI AKADEMIK SISWA SMA KELAS XII - Aldi Aulia Muhammad; Siti Fatimah; Tuti Alawiyah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2022)
For students who have problems regarding academic procrastination at school, this service is very appropriate, because the problems they experience are related to a sense of laziness in procrastinating assignments on the series. The purpose of this study was to determine the implementation, responses, constraints, and difficulties in implementing group guidance services for students who have problems regarding academic procrastination. The approach used in this study is descriptive qualitative using the phenomenological method, in this study the data collection techniques used were observation, interviews, and documentation. The results showed that group guidance services using self-management techniques for students who experienced academic procrastination carried out in groups were effective because they provided information about the importance of changing student behavior in lazy learning which caused task delays to become better, after carrying out group guidance services students were more can be active, can adjust the time in doing tasks, and have good self-controlKeywords: Academic procrastination, group guidance services